Antibiotic resistance profile, potential drivers and genotype of Escherichia coli, Salmonella sp. and Vibrio sp. isolated from hybrid red tilapia and Asian seabass in the West Coast of Peninsular Malaysia - Dewi, Rita Rosmala (2022)
The intensive system of farm-raised fish accelerates the use of antibiotics which in turn increases the emergence of antimicrobial resistance (AMR) within bacteria in an aquatic environment. The current study was designed to investigate the prevalence of E. coli, Salmonella and Vibrio sp. among the cultured freshwater and brackish water fish in the central part of Peninsular Malaysia; determine the resistance pattern of E. coli, Salmonella and Vibrio isolates against selected antibiotics; identify aquaculture management practices and the environmental factors associated with the multidrug resistance (MDR); and characterize the isolates by molecular typing method to identify their profile and sequence type. Over a period of 12 months, a total of 32 fish farms from Selangor, Negeri Sembilan, Melaka and Perak were sampled. A total of 609 samples were collected from tilapia (312), Asian seabass (265) and pond waters (32). The samples were analyzed using established microbiology protocols to confirm E. coli, Salmonella sp, Vibrios sp. Disk diffusion and broth microdilution method (BMD), were used to determine the antibiotic resistance pattern of the isolates. Then, V. parahaemolyticus that harbored virulence genes were detected and characterized using Multi-Locus Sequence Typing (MLST) method. Risk factor for MDR E. coli (n=249) and V. parahaemolyticus (n=162) isolates were investigated applying multilevel binary logistic regression to observed the association of management and environmental factors to MDR development. The result of this study highlighted the aquaculture production system is an important reservoir of clinically important bacteria. The findings revealed that bacteria isolated had a high level of resistance to antibiotics classified as priority and critically important for human use, as well as veterinary critically important medications for food-producing animals, posing a significant risk to human, aquatic and animal health. Moreover, the virulent strain of V. parahaemolyticus found in this study are those that are circulating in the Asian geographical region from intercontinental dissemination. Possible interventions implementable at the aquaculture farm to reduce MDR E. coli include reducing on- farm practice such as manuring of fish pond. For V. parahaemolyticus, aquaculture farm adjacent to human activities, large-scale farms and farms with earthen ponds were at increasing odds for MDR development. This study findings propose potential practical and targeted interventions by aquaculture farmers to reduce AMR and mitigate development of MDR of significant bacteria of fish, animal and public health concern to better sustain the aquaculture industry while at the same time improve the welfare of animals and the health of environment and humans